2009
DOI: 10.1007/s10237-009-0182-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-regulation of mesenchymal stem cell differentiation and collagen organisation during skeletal tissue repair

Abstract: A number of mechano-regulation theories have been proposed that relate the differentiation pathway of mesenchymal stem cells (MSCs) to their local biomechanical environment. During spontaneous repair processes in skeletal tissues, the organisation of the extracellular matrix is a key determinant of its mechanical fitness. In this paper we extend the mechano-regulation theory proposed by Prendergast et al (1997) to include the role of the mechanical environment on the collagen architecture in regenerating soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Using this mechano-regulation model (Prendergast et al, 1997), it has been possible to predict the spatial and temporal patterns of tissue differentiation during a number of regenerative events such as fracture healing Nagel and Kelly 2009), osteochondral defect repair (Kelly and Prendergast 2005;Kelly and Prendergast 2006) and distraction osteogenesis (Boccaccio et al, 2007;Boccaccio et al, 2008). However even with the use of complex computational models, it is difficult to determine how specific mechanical signals influence MSC differentiation in vivo within the milieu of other regulatory factors that are present.…”
Section: Repairmentioning
confidence: 99%
“…Using this mechano-regulation model (Prendergast et al, 1997), it has been possible to predict the spatial and temporal patterns of tissue differentiation during a number of regenerative events such as fracture healing Nagel and Kelly 2009), osteochondral defect repair (Kelly and Prendergast 2005;Kelly and Prendergast 2006) and distraction osteogenesis (Boccaccio et al, 2007;Boccaccio et al, 2008). However even with the use of complex computational models, it is difficult to determine how specific mechanical signals influence MSC differentiation in vivo within the milieu of other regulatory factors that are present.…”
Section: Repairmentioning
confidence: 99%
“…In recent findings by our group we could demonstrate that the IVD environment along with mechanical loading represents a major "discogenic" differentiation stimulus for hMSC; this stimulus being much stronger than the pre-conditioning in presence of 100ng/ Ml GDF5 added to the media [35]. Several studies have shown that mechanical loading applied on stem cells might improve the outcome of chondrogenesis of stem cells [18,19,36]. Especially effective was the pre-conditioning of hMSCs embedded in PEG hydrogel the microenvironment of the IVD but also be non-viral transfection using GDF5 overexpression vector [17].…”
Section: Gdf5 and Mechanical Loading Stimulationsmentioning
confidence: 86%
“…On the other hand, the presence of human recombinant growth and differentiation factor 5 (rhGDF5=CDMP1=BMP14) [15][16][17] and dynamic loading [18,19] have been described as one of the potent factors that could direct discogenic differentiation of hMSCs. Recently, a consortium was formed to define the discogenic phenotype [20] more closely.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are important not only for healing but also in bone formation, regeneration, remodeling and some pathological changes in bones. Phenomena as for example tissue differentiation from mesenchymal stem cells and revascularization, which often play key roles in final effects of considered processes, are quite dependent on mechanical factors, see e.g., [6][7][8]23,25,26,37,40]. There are already many experimental and clinical investigations reported, see e.g., [2,6,8].…”
mentioning
confidence: 99%